Impact of Forest and Land Fires on Environmental Pollution and Public Health in Sungai Raya Sub-District, Kubu Raya District - Yulianti, Yulianti; Rupita, Rupita; Rahmaniah, Syarifah Ema; Syarmiati, Syarmiati; Sudirman, Sudirman (PT. Riset Press International, 2024)
Forest and land fires in Sungai Raya District, Kubu Raya Regency, severely impact environmental pollution and public health. This condition causes quite significant ecological and social losses. First, the smoke produced from these fires contains various dangerous substances, such as carbon monoxide, dust particles, and toxic chemicals. Continuous exposure to these substances can cause respiratory problems, respiratory tract diseases, and other health problems in local communities. Apart from that, forest fires also result in the loss of natural habitat for various species of flora and fauna. Disrupted ecosystems can cause biodiversity loss and affect local food chains. Recovery of fire-affected ecosystems takes a long time, and some species may experience local extinction due to habitat loss. Furthermore, preventing and responding to forest fires requires significant resources in terms of personnel and equipment. Funds allocated for firefighting can disrupt local government budgets that should be used for infrastructure development and community welfare programs. Therefore, forest fires harm the environment and health and impose an economic burden on the people of Sungai Raya District. Efforts to prevent forest and land fires and educate the public regarding the risks of prevention are essential to overcome these negative impacts. Sustainable measures such as law enforcement against illegal forest burning, sustainable land management, and increasing public awareness of the importance of preserving the environment can help reduce fire risks and protect public health.